Development of Web Based Secret Snake Ladder Media for Learning to Make Simple Mandarin Sentence - Widuri, Ananda Wahyu Puspa; Pratita, Ina Ika; Amri, Miftachul (UNDIKMA, 2025)
Mandarin is increasingly significant in the global and bilateral context between Indonesia and China. However, students often face challenges in mastering basic vocabulary essential for forming simple sentences. This study aims to develop an interactive web-based learning media called